Indonesian Labor Conditions on February 2016-2019 using Linear Trend Forecasting - Putra, Rizaldi; Renaldo, Nicholas (Reflection: Education and Pedagogical Insights, 2024)
The purpose of this study is to analyze the labor conditions in Indonesia from February 2016 to February 2019 using the Linear Trend Forecasting method. This study employs a quantitative research approach using Linear Trend Forecasting to analyze Indonesia's labor conditions from February 2016 to February 2019. The objective is to identify trends in the unemployment rate, labor force growth, sectoral employment shifts, and educational disparities in unemployment. The Linear Trend Forecasting analysis reveals a declining trend in Indonesia’s unemployment rate from 2016 to 2019, with projections indicating further reductions in 2020. Urban unemployment remains higher (6.205%) than rural unemployment (3.135%), highlighting disparities in labor absorption. Human Capital Theory suggests that differences in employment rates are influenced by education, skill development, and labor market readiness. The findings emphasize the importance of workforce training, education reform, and government policies in reducing unemployment. Future studies can explore the impact of digital transformation on employment trends in Indonesia.